Inhibition of microRNA-299-5p sensitizes glioblastoma cells to temozolomide via the MAPK/ERK signaling pathway. Issue 5 (12th September 2018) - Peng, Yujiang; He, Xijun; Chen, Huihui; Duan, Hongyu; Shao, Bo; Yang, Fan; Li, Huiyong; Yang, Pengxiang; Zeng, Yu; Zheng, Jinrong; Li, Yongsheng; Hu, Jiachang; et al.
Abstract : Glioblastomas (GBMs) are a lethal class of brain cancer, with a median survival <15 months in spite of therapeutic advances. The poor prognosis of GBM is largely attributed to acquired chemotherapy resistance, and new strategies are urgently needed to target resistant glioma cells. Here we report a role for miR-299-5p in GBM. The level of miR-299-5p expression was detected in glioma specimens and cell lines by qRT-PCR. Luciferase reporter assays and Western blots were performed to verify GOLPH3 as a direct target of miR-299-5p. In vitro cell proliferation, invasion, cell cycle distribution, and apoptosis were assessed to determine whether or not miR-299-5p knockdown sensitized GBM cells to temozolomide (TMZ). We demonstrated that miR-299-5p levels were up-regulated in the GBM groups compared with the normal control group. The highest expression of miR-129-5p occurred in the highest GBM stage. miR-299-5p knockdown significantly inhibited the MAPK/extracellular signal-regulated kinase (ERK) signaling pathway. We also showed that miR-299-5p knockdown enhanced sensitivity of GBM cells to TMZ both in vitro and in vivo by inhibiting cell proliferation and invasion and promoting apoptosis. In addition, we demonstrated that GOLPH3 is a novel functional target of miR-299-5p . GOLPH3 regulates the MAPK/ERK axis under miR-299-5p regulation. In conclusion, we identified a link between miR-299-5p expression and the GOLPH3/MAPK/ERK axis, thus illustrating a novel role for miR-299-5p in GBM.